La «Roma del Perú» au tournant du siècle : catholicisme, libéralisme et identité locale à Arequipa (1890-1915) - Guillemette Martin (Amnis)
This paper proposes an approachboth local anddiscursive of the tensionsinvolved in the processof secularizationin Peruat the turn of the nineteenth and twentieth centuries,from the case study– bothextreme andrepresentative – of Arequipa.During this period, the press of Arequipais the setting for an intense debateamong liberals, concerned about the entrance of the cityin modern times,and theconservative Catholics and, who see this debate as adirect threatto the traditional political and moral power they hadfor generationsin the region.Because of the violenceof the debates thatopposeliberaland conservative Catholics, but also because of the clear regional and identity dimension of the conflict in themistiana capital, Arequipa is certainly afertile groundfor the analysis ofthe limits,and eventhe failures of the secularizationprocesscompletely out of phase withlocal aspirations.